2020
DOI: 10.3390/cancers12102786
|View full text |Cite
|
Sign up to set email alerts
|

Granzyme B Degraded Type IV Collagen Products in Serum Identify Melanoma Patients Responding to Immune Checkpoint Blockade

Abstract: A T-cell permissive tumor microenvironment, characterized by the presence of activated T cells and low fibrotic activity is crucial for response to immune checkpoint inhibitors (ICIs). Granzyme B has been shown to promote T-cell migration through the basement membrane by the degradation of type IV collagen. In this study, we evaluated the biomarker potential of measuring granzyme B-mediated degradation of type IV collagen (C4G) in combination with a fibroblast activation biomarker (PRO-C3) non-invasively for i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 34 publications
0
38
0
Order By: Relevance
“…During ECM turnover, proteolytically cleaved matrix degradation fragments are released into the systemic circulation (Bonnans, Chou et al 2014).Serum levels of collagen degradation fragments are elevated in cancer patients compared to healthy controls, and checkpoint blockade alters serum CDP levels (Jensen, Madsen et al 2018, Jensen, Sinkeviciute et al 2020, Wang, Bager et al 2021). NC410 treatment increased specific fragments generated by degradation of collagen VI by MMP-2 (C6M) and collagen IV by granzyme B (C4G).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During ECM turnover, proteolytically cleaved matrix degradation fragments are released into the systemic circulation (Bonnans, Chou et al 2014).Serum levels of collagen degradation fragments are elevated in cancer patients compared to healthy controls, and checkpoint blockade alters serum CDP levels (Jensen, Madsen et al 2018, Jensen, Sinkeviciute et al 2020, Wang, Bager et al 2021). NC410 treatment increased specific fragments generated by degradation of collagen VI by MMP-2 (C6M) and collagen IV by granzyme B (C4G).…”
Section: Discussionmentioning
confidence: 99%
“…We therefore hypothesize that specific granzyme B degraded type IV collagen fragments and other fragments are released to the circulation when T cells infiltrate tumors and may have potential as a clinical pharmacodynamic biomarker. Interestingly, granzyme B degraded type IV collagen fragments (C4G) associate with favorable anti-CTLA-4 treatment response in metastatic melanoma patients (Jensen, Madsen et al 2018, Jensen, Sinkeviciute et al 2020. (St-Pierre and Potworowski 2000)The potential of C6M and C4G collagen fragments as biomarkers of clinical response will be further investigated in a recently initiated NC410 first-in-human clinical trial (NCT04408599).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, our group has recently showed the importance of targeting specific PTMs of Type IV collagen and vimentin in metastatic melanoma and lung cancer. We demonstrated that two different neo‐epitopes on the same protein (Type IV collagen and vimentin) could in fact provide opposite prognostic value 37,38 . These data underline the importance of targeting the relevant epitope in cancer biomarker discovery.…”
Section: Discussionmentioning
confidence: 66%
“…We demonstrated that two different neo-epitopes on the same protein (Type IV collagen and vimentin) could in fact provide opposite prognostic value. 37,38 These data underline the importance of targeting the relevant epitope in cancer biomarker discovery. Furthermore, it urges for caution when targeting the full-length protein, instead of targeting protein fragments as also suggested by Hosein et al 6 In our study, we observed that targeting two different neo-epitopes located in the propeptide of Type XI collagen had completely differential biomarker value.…”
Section: Discussionmentioning
confidence: 84%